Пошаговое объяснение:
а)
{5у - 3х = 35
{х + 3у = 7
{х = 7 - 3у
1)
5у - 3х = 35
5у - 3(7 - 3у) = 35
5у - 21 + 9у = 35
5у + 9у = 35 + 21
14у = 56
у = 56 : 14
у = 4
2)
х = 7 - 3у
х = 7 - 3 * 4
х = 7 - 12
х = -5
(-5; 4)
б)
{5х - 2у = 15
{2х - у = 7 | * -2
{-4х + 2у = -14
{х = 1
5х - 2у = 15
5 * 1 - 2у = 15
5 - 2у = 15
2у = 5 - 15
2у = -10
у = -10 : 2
у = -5
(1; -5)
Пошаговое объяснение:
а)
{5у - 3х = 35
{х + 3у = 7
{5у - 3х = 35
{х = 7 - 3у
1)
5у - 3х = 35
5у - 3(7 - 3у) = 35
5у - 21 + 9у = 35
5у + 9у = 35 + 21
14у = 56
у = 56 : 14
у = 4
2)
х = 7 - 3у
х = 7 - 3 * 4
х = 7 - 12
х = -5
(-5; 4)
б)
{5х - 2у = 15
{2х - у = 7 | * -2
{5х - 2у = 15
{-4х + 2у = -14
{х = 1
{5х - 2у = 15
5х - 2у = 15
5 * 1 - 2у = 15
5 - 2у = 15
2у = 5 - 15
2у = -10
у = -10 : 2
у = -5
(1; -5)